Public management of smart cities: European experience - S. A. Zakharova (Цифровая социология, 2022)
The article presents a rethinking of the results of research in the ﬁeld of smart city management based on publications in Spain and the Netherlands. Three areas of research have been identiﬁed. The ﬁrst one offers scientiﬁc studies of smart city management and recommendations for improving the effectiveness of smart management based on a clear understanding of the degree of legitimacy of decision-making. The author considers these processes in comparison with the Russian scientists approaches, and focuses on the important conclusion of foreign scientists that technology alone will not make the city smarter: the construction of a smart city requires a political understanding of technology, a process approach to management, an emerging smart city, and a focus on both economic beneﬁts and other public values. The second group of articles, considered by the author, presents a more comprehensive view of the concepts of smart cities, with smart governance, combining, presumably, innovative structures and new technologies, new communication channels aimed at the constant functioning of the city management system and the environment for cooperation and citizen engagement. The third group of publications deals with critical aspects of the development of smart governance in practice and the resulting consequences, in particular, the reassessment of the ability of the private sector to develop and implement intelligent technologies, the predominance of a technocratic approach to decision-making, the inability to ensure impartiality and objectivity, the lack of the ability to analyse urban data, cloud computing on digital platforms to stimulate production in a collaborative environment. Their conclusion about the need for “smart management” to pay attention to the processes of socio-spatial development is quite correlated with the conclusions of Russian scientists.